(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Artificial intelligence (AI) has demonstrated considerable potential in enhancing educational practices, while the integration of socio-scientific issues (SSI) in science instruction provides meaningful learning experiences that promote higher-order thinking and societal responsibility. This study examined the effects of an AI-mediated instructional approach integrating Socio-Scientific Issues within Green Chemistry Education (AI-SSI in GCE) on learners’ chemical literacy (CL) and scientific argumentation skills (SAS). A one-group pretest–posttest quasi-experimental design was employed involving 31 Grade 11 learners. Data were collected using a Hydrocarbons Chemical Literacy Test (H-CLT), a 30-item multiple-choice instrument aligned with established chemical literacy domains, and a Claim–Evidence–Reasoning–based Argumentative Writing Assessment (CER-AWA). The results revealed statistically significant improvements with large effect sizes in both chemical literacy and scientific argumentation skills following the intervention. Learners demonstrated enhanced abilities to apply chemical knowledge across content, contextual, higher-order, and affective domains, particularly in addressing real-world environmental issues such as plastic pollution. Analysis of scientific argumentation indicated that learners were able to construct complete claims, select relevant evidence, and partially articulate coherent scientific reasoning linking evidence to claims. Additionally, learners exhibited increased awareness of green chemistry principles, environmental sustainability, and the societal implications of chemical decision-making. In conclusion, the AI-SSI in GCE instructional approach effectively fostered cognitive, argumentative, green chemistry awareness, and socio-affective learning outcomes. The findings support the integration of socio-scientific issues and green chemistry concepts into chemistry instruction and highlight the potential of AI as a pedagogical scaffold. However, ethical considerations related to AI use in education may be addressed, and continued optimization and professional dialogue among educators are essential to ensure responsible and learner-centered implementation.